PENYULUHAN HUKUM MENGENAI KETENAGAKERJAAN DI RT 07 RW 14 KELURAHAN BAHAGIA KECAMATAN BABELAN KABUPATEN BEKASI - Andriyanto Adhi Nugroho; Surahmad (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
The devotion to the community aims to provide mentoring and socialization of the rights that are being addressed by Labor based on legislation on Labor. Analysis of the arrangement was done with the instrument of law based on the Constitution of the Republic of Indonesia year 1945, Act No. 13 year 2003 on employment. Protection against workers is intended to ensure the basic rights of workers and ensure the similarities of opportunities and treatment without discrimination of any kind to realize the welfare of workers and their families while still paying attention to developments Business progress and entrepreneurs' interests. The legislation related to the protection of the workers of Law No. 13 year 2003 on employment and implementing regulations of the law in the field of employment. The devotion to this community is done by several phases, which are divided into three phases, namely (1) the preparatory phase for community service, the preparation phase begins with finding the problem that will be discussed in the devotion to This society. Further followed by the collapse of the title and formulation of the proposal to community devotion. (2) The stage of implementation, this stage begins with the data-keeping through the dedication of the literature by reviewing the relevant library materials with the research study then supplemented by interviews to the informant to complete the data This devotion. (3) Completion stage, at the stage of this research is conducted by analyzing the research data followed up by the preparation of reports and publications of the results of community devotion.